2018
DOI: 10.1161/circimaging.118.007913
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of VWF (von Willebrand Factor) and Platelet Adhesion in Postischemic Impaired Microvascular Reflow

Abstract: Background: Complete mechanistic understanding of impaired microvascular reflow after MI will likely lead to new therapies for reducing infarct size. Myocardial contrast echocardiography (MCE) perfusion imaging and molecular imaging were used to evaluate the contribution of microvascular endothelial-associated Von Willebrand Factor (VWF) and platelet adhesion to microvascular “no-reflow”. Methods and Results: MI was produced by transient LAD ligation in wild-type mice, wild-type mice treated with rADAMTS13 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…The ability to image thrombus may also be important for monitoring the efficacy of antithrombotic therapies. It has been used in preclinical studies to evaluate new strategies aimed at inhibiting platelet-mediated thrombosis in atherosclerotic disease and in thrombotic complications of anti-cancer drugs (Moccetti et al 2018a(Moccetti et al , 2018bOzawa et al 2018;Latifi et al 2019). Finally, the targeting of MBs to a specific disease process could also be important in increasing their use in ultrasound-mediated therapy such as delivery of fibrinolytics or sonothrombolysis (Marsh et al 2007;Xie et al 2009;Kawata et al 2012).…”
Section: Molecular Imaging Of Thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to image thrombus may also be important for monitoring the efficacy of antithrombotic therapies. It has been used in preclinical studies to evaluate new strategies aimed at inhibiting platelet-mediated thrombosis in atherosclerotic disease and in thrombotic complications of anti-cancer drugs (Moccetti et al 2018a(Moccetti et al , 2018bOzawa et al 2018;Latifi et al 2019). Finally, the targeting of MBs to a specific disease process could also be important in increasing their use in ultrasound-mediated therapy such as delivery of fibrinolytics or sonothrombolysis (Marsh et al 2007;Xie et al 2009;Kawata et al 2012).…”
Section: Molecular Imaging Of Thrombosismentioning
confidence: 99%
“…More recently, these agents have been used not only to detect microvascular thrombosis in postinfarct microvascular no-reflow, but also to evaluate the role of new therapies for this condition (Fig. 4) (Ozawa et al 2018). They have also been used to detect renal platelet adhesion from VWF (Latifi et al 2019), giving hope that they could be eventually applied for more accurate diagnosis of thrombotic microangiopathies.…”
Section: Molecular Imaging Of Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CEU molecular imaging with targeted MBs for platelet GPIbα and VWF have been applied to rapidly evaluate microvascular no-reflow phenomenon in rodent model of post-MI reperfusion, and the efficacy of new approaches to improving reflow. [39]. Additionally, CEU molecular imaging for platelet GPIbα and VWF have been developed to reveal a new form of vascular toxicity for the third-generation tyrosine kinase inhibitor ponatinib that involves VWF-mediated platelet adhesion and a secondary microvascular angiopathy that produced ischemic wall motion abnormalities [30].…”
Section: Thrombus Imagingmentioning
confidence: 99%
“…A. Sambola et al revealed a correlation between elevated von Willebrand factor concentration in blood plasma and thrombus resistance to fibrinolysis in patients with CI with ST elevation [38]. K. Ozawa et al, in their turn, revealed that an increase in endotheliumassociated von Willebrand factor concentration slowed down blood flow in the microcirculatory channel after CI [39]. Chinese researchers performed substantial meta-analysis aimed at estimating von Willebrand factor kinetics af-ter CI.…”
mentioning
confidence: 99%